Extraction and Characterization of Chitosan from Crab Shells: Kinetic and Thermodynamic Studies of Arsenic and Copper Adsorption from Electroplating Wastewater - A., Sumaila; M., Ndamitso M.; A., Iyaka Y.; S., Abdulkareem, A.; O., Tijani J.; O., Idris M. (Iraqi Journal of Science, 2020)
Crab shells were used to produce chitosan via the three stages of deproteinization, demineralization and deacetylation using sodium hydroxide and hydrochloric acid under different treatment conditions of temperature and time. The produced chitosan was characterized using Fourier transform infrared spectroscopy (FTIRS), X-ray diffraction (XRD), high – resolution scanning electron microscopy (HRSEM), electron dispersion spectroscopy (EDS), dynamic light scattering (DLS), Brunauer Emmett Teller (BET) and Thermogravimetric analysis (TGA). The adsorption behavior of chitosan to remove arsenic (As) and copper (Cu) from electroplating wastewater was examined by batch adsorption process as a function of adsorbent dose, contact time and temperature. The FTIR, XRD, HRSEM and EDS analyses confirmed, respectively, the presence of –NH2 and –OH functional groups, with amorphous/crystalline phases, crystallinity index of 69.54%, needle-like morphology and Carbon (C), Oxygen (O) and Nitrogen N) in the produced chitosan. While DLS, BET and TGA showed, respectively, that the produced chitosan has an average particle size of 729nm, is moderately polydisperse, has12.67 m2/g surface area, mesoporous in nature, and with thermal stability of up to 1430C. The optimum adsorbent dose, contact time and temperature values to remove As and Cu by chitosan were 15mg, 45 minutes, 333K and25mg, 60 minutes, 349K,respectively. Under the employed conditions, chitosan though has a low surface area, displaying high adsorption capacity for both metal ions. The adsorption isotherm data were better fitted to the Jovanovic isotherm model while the kinetic data fitted best to the pseudo-second order model. The thermodynamic studies established that the adsorption was feasible but endothermic in nature. This study shows that chitosan adsorbents purify electroplating wastewater.